Theory of Fighting the Epidemic with Traditional Chinese Medicine Qigong (气功) Therapy - Dan Zhao (Wolters Kluwer Health/LWW, 2021)
Qigong (气功) therapy is an active self-paced exercise therapy and it has a long history in traditional Chinese medicine (TCM). As early as the mention of it in the Huang Di Nei Jing (《黄帝内经》 Huangdi's Internal Classic), there is a record of using qigong therapy to prevent and treat pestilence. This thesis discusses the idea and methods of qigong therapy in TCM, such as daoyin (导引), expiration and inspiration, and meditation. These methods purpose to have the functions of strengthening and consolidating the primordial qi, improving health conditions, and resisting pestilent qi. Therefore, the core idea of fighting the epidemic with qigong therapy is to enhance the healthy qi, and to prevent the intrusion of pestilent qi into the human body. It embodies the TCM thought of "when there is sufficient healthy qi inside the body, the evil cannot invade the body."